2013
DOI: 10.1364/boe.5.000275
|View full text |Cite
|
Sign up to set email alerts
|

In vitro glucose measurement using tunable mid-infrared laser spectroscopy combined with fiber-optic sensor

Abstract: Because mid-infrared (mid-IR) spectroscopy is not a promising method to noninvasively measure glucose in vivo, a method for minimally invasive high-precision glucose determination in vivo by mid-IR laser spectroscopy combined with a tunable laser source and small fiber-optic attenuated total reflection (ATR) sensor is introduced. The potential of this method was evaluated in vitro. This research presents a mid-infrared tunable laser with a broad emission spectrum band of 9.19 to 9.77[Formula: see text](1024~10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In our study, the wavelength tunable CO 2 laser was customized from Access Laser Co. in Washington in USA. The emission wavenumbers were tuned by linear motor to rotate a grating, and the frequency and power of the tuned lines were stabilized using a photoelectric detection feedback system and a piezo actuator to modulate the cavity length [41]. In this study, the CO 2 laser achieved line tuning over the band of 9.19-9.77 m; five emission wavenumbers around the glucose absorption peaks 1080 and 1035 cm −1 , including 1081, 1076, 1051, 1041 and 1037 cm −1 were selected as working wavenumbers for glucose specific determination [16].…”
Section: Experimental Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, the wavelength tunable CO 2 laser was customized from Access Laser Co. in Washington in USA. The emission wavenumbers were tuned by linear motor to rotate a grating, and the frequency and power of the tuned lines were stabilized using a photoelectric detection feedback system and a piezo actuator to modulate the cavity length [41]. In this study, the CO 2 laser achieved line tuning over the band of 9.19-9.77 m; five emission wavenumbers around the glucose absorption peaks 1080 and 1035 cm −1 , including 1081, 1076, 1051, 1041 and 1037 cm −1 were selected as working wavenumbers for glucose specific determination [16].…”
Section: Experimental Systemmentioning
confidence: 99%
“…The emission wavenumbers were tuned by linear motor to rotate a grating, and the frequency and power of the tuned lines were stabilized using a photoelectric detection feedback system and a piezo actuator to modulate the cavity length [41]. In this study, the CO 2 laser achieved line tuning over the band of 9.19-9.77 m; five emission wavenumbers around the glucose absorption peaks 1080 and 1035 cm −1 , including 1081, 1076, 1051, 1041 and 1037 cm −1 were selected as working wavenumbers for glucose specific determination [16]. The five wavenumbers between the two absorption wavenumbers (1035 cm −1 and 1080 cm −1 ) could be tuned randomly in the theory, but after lots of experiment we found that the five wavenumbers (1081, 1076, 1051, 1041 and 1037 cm −1 ) which we selected can achieve both high stability of line frequency and power simultaneously compared to other wavenumbers.…”
Section: Experimental Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate these issues, optical detection schemes have been adopted for their salient features, including an enzyme-free process, fast response, and the potential for noninvasive detection. Absorption spectroscopy based on Beer's Law assumes a linear relationship between glucose concentration and absorbance [9][10][11][12][13][14], which is only good for concentrations below hundreds of mg/dL [15]. It has been noted that a bulky, expensive spectrometer is required to continuously monitor the absorption spectrum [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of applying MIR-ATR methods for blood glucose measurement including ones measuring glucose levels of whole blood, [8][9][10] urine, 11 and serum. 12,13 Some groups reported that they have attempted to measure blood glucose levels in vivo by using an ATR prism with MIR lasers 14,15 and an FT-IR spectrometer. 16 These methods mainly detect glucose in interstitial fluid that reflects the blood glucose level 17 because the penetration depth of MIR-ATR spectroscopy is limited to a few microns.…”
Section: Introductionmentioning
confidence: 99%